2021
DOI: 10.1042/bst20200737
|View full text |Cite
|
Sign up to set email alerts
|

Heterochromatin and Polycomb as regulators of haematopoiesis

Abstract: Haematopoiesis is the process by which multipotent haematopoietic stem cells are transformed into each and every type of terminally differentiated blood cell. Epigenetic silencing is critical for this process by regulating the transcription of cell-cycle genes critical for self-renewal and differentiation, as well as restricting alternative fate genes to allow lineage commitment and appropriate differentiation. There are two distinct forms of transcriptionally repressed chromatin: H3K9me3-marked heterochromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 102 publications
(110 reference statements)
0
4
0
Order By: Relevance
“… 18 H3K9Me3 is suggested to reduce the plasticity of progenitors during lineage commitment, and inhibition of SUV39H1 enhances the generation of induced pluripotent stem cells. 19 , 20 The predicted inhibition of SUV39H1 expression by the GATA1 antisense transcript was tested by CRISPR-mediated deletion of the antisense promoter from K562 cells. Decreased GATA1 antisense transcripts were associated with increased SUV39H1 transcripts ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“… 18 H3K9Me3 is suggested to reduce the plasticity of progenitors during lineage commitment, and inhibition of SUV39H1 enhances the generation of induced pluripotent stem cells. 19 , 20 The predicted inhibition of SUV39H1 expression by the GATA1 antisense transcript was tested by CRISPR-mediated deletion of the antisense promoter from K562 cells. Decreased GATA1 antisense transcripts were associated with increased SUV39H1 transcripts ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…The GATA1 antisense transcript was shown to inhibit SUV39H1 expression in the human K-562 cell line. Additionally, the inhibition of SUV39H1 expression facilitates the generation of induced pluripotent stem cells, and increased H3K9Me3 reduces the plasticity of progenitor cells [22,23]. Therefore, it was proposed that GATA1 antisense expression may regulate differentiation through the inhibition of both GATA1 sense and SUV39H1 transcription [7].…”
Section: Gata Switches and The Role Of Noncoding Rna In Differentiationmentioning
confidence: 99%
“…It was shown that SUV4-20H1 promotes locus-specific heterochromatin formation on the MyoD locus by deposition of H4K20me2, leading to its transcriptional silencing and, as a result, the maintenance of quiescence [49]. In addition, repressive mechanisms also play key roles in proliferation and differentiation of adult stem cells, including hematopoietic [50], skin [51,52], and intestinal stem cells [53,54]. For instance, it has been shown that PRC2-mediated H3K27me3 in stem cells of the small intestine maintain proliferation of intestinal progenitor cells by preventing the expression of differentiation-related genes [53,54].…”
Section: Epigenetic Alterations In the Skeletal Muscle During Agingmentioning
confidence: 99%